Laws of evolution of slip trace pattern and its parameters with deformation in [1.8.12] – single crystals of Ni[3]Fe alloy; AIP Conference Proceedings; Vol. 1698 : Advanced Materials in Technology and Construction, AMTC-2015 - Teplyakova L. A. Lyudmila Alekseevna (2016, 2016)
Title screen